The preparticipation evaluation of the young athlete—an update to what the orthopedic surgeon needs to know - Plassche, Grace C.; Miller, Daniel James; Christian, Robert A.; Trofa, David P.; Redler, Lauren H.; Levine, William N.; Ahmad, Christopher S.; Popkin, Charles A. (Frontiers in Sports and Active Living, 2025)
The preparticipation evaluation (PPE) continues to be a recommended and widely used tool in identifying athletes with health conditions or injury risks that may impact their athletic participation. In the last 10 years, updates to the PPE mirror the increasing impacts of sport specialization, level of competition, importance of mental health in injury risk and recovery, research on cardiovascular and concussive health in youth athletes, and increased awareness of metabolic demands placed on both male and female athletes. The PPE at this snapshot in time exists within an evolving landscape of recommendations. However, it continues to present a vital opportunity for health care providers, preferably within the athlete's “medical home”, to discuss anticipatory guidance, intervene on injury risk, and establish a baseline for future monitoring as the athlete enters competition. As mentioned, there continues to be a need for further research and development, but the orthopedic surgeon should be aware of the purpose the PPE currently serves given the intersectionality of their field with young athletes at the brink or in the midst of injury.